Peran Guru Kristen dalam Membangun Karakter Siswa di Sekolah Multikultural - Orpa Umbu Lado; Maria Titik Windarti (Journal New Light, 2024)
This research examines the role of Christian teachers in building student character in multicultural schools. Using a holistic approach, this research explores how the integration of Christian values ​​in the formal and informal curriculum, as well as the development of programs that support diversity, can shape students’ overall character. The research results show that Christian teachers who consistently apply values ​​such as love, honesty, integrity, and tolerance in their teaching not only improve students’ academic aspects but also strengthen their morals and ethics. In addition, Christian teachers’ participation in extracurricular programs has been proven to have a significant positive influence on the formation of students’ character, especially through activities that encourage cooperation, empathy and respect for differences. This research confirms the importance of a holistic approach in character education in multicultural schools and the significant contribution of Christian values ​​in forming an ethical and tolerant generation.